1997
DOI: 10.1139/y97-067
|View full text |Cite
|
Sign up to set email alerts
|

Tachykinin receptors and intestinal motility

Abstract: Substance P (SP) and neurokinin A (NKA) are synthesized by enteric cholinergic motorneurons that project to the longitudinal and circular muscle of the mammalian intestine. Thus, acetylcholine, SP, and NKA are the excitatory neuromuscular transmitters in the intestine. Tachykinin NK1 and NK2 receptors are expressed by smooth muscle cells in most regions of the intestine: the corelease of SP and NKA from nerves thus realizes paradigms of tachykininergic cotransmission. Examples have been found in which a cooper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Few studies have examined the transduction mechanisms underlying tachykinin-evoked smooth muscle contraction and to our knowledge, none of these have investigated human esophageal muscle. Previous studies suggested that Ca 2ϩ influx through L-type Ca 2ϩ channels was critical for tachykinin-evoked contraction in guinea pig, rabbit, and human colonic smooth muscles (Maggi et al, 1997;O'Riordan et al, 2001). In contrast, a major role for Ca 2ϩ stores has been suggested in human sigmoid colon muscle by Cao et al (2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have examined the transduction mechanisms underlying tachykinin-evoked smooth muscle contraction and to our knowledge, none of these have investigated human esophageal muscle. Previous studies suggested that Ca 2ϩ influx through L-type Ca 2ϩ channels was critical for tachykinin-evoked contraction in guinea pig, rabbit, and human colonic smooth muscles (Maggi et al, 1997;O'Riordan et al, 2001). In contrast, a major role for Ca 2ϩ stores has been suggested in human sigmoid colon muscle by Cao et al (2000).…”
Section: Discussionmentioning
confidence: 99%
“…In guinea pig ileum as well as rabbit and human colon, excitation involves influx of extracellular Ca 2ϩ through nifedipinesensitive, L-type Ca 2ϩ channels (Maggi et al, 1997;O'Riordan et al, 2001). In contrast, contractions of human sigmoid colon are less dependent on Ca 2ϩ influx but are abolished by blockade of the sarcoplasmic reticulum Ca ATPase by thapsigargin (Cao et al, 2000).…”
mentioning
confidence: 99%
“…TKs act as neurotransmitters on neurons and cells (such as smooth muscle, secretory epithelium, and glands) in the gastrointestinal tract of mammals [1][2][3] . They are important excitatory neurotransmitters in the enteric nervous system, are involved in the coordination of gastrointestinal motility, and are powerful spasmogens in almost every region of the mammalian intestine [1][2][3][4][5][6] . Substance P (SP), neurokinin A (NKA) and neurokinin B (NKB) are tachykinins derived from two preprotachykinin (PPT) genes [1,[7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Tachykinins (substance P, neurokinin A (NKA), and neurokinin B) act as neurotransmitters in the enteric nervous system (14,15), spinal cord, and brain (16 -18). They exhibit preferential binding to three receptor subtypes, NK1, NK2, and NK3, respectively.…”
mentioning
confidence: 99%